Development Of An Inhibitive Acetylcholinesterase-Based Assay For Insecticides - Tham, Lik Gin (2008)
An inhibition study on Pangasius pangasius brain Acetylcholinesterase (AChE) was conducted. A custom-synthesized affinity column chromatography utilizing activated Sephacryl S-1000 was successfully coupled to procainamide. AChE loaded onto the column and run with a flow rate of 0.2 ml/min was shown to give a good binding capacity with a recovery yield of 51.97% and a purification fold of 7.52. Overall, total protein content (mg) decreases while specific activity increased, thus conforming to a typical successful purification process. Further analysis with effect o of substrate using Acetylthiocholine Iodide (ATC), Butyrylthiocholine Iodide (BTC) and Propionylthiocholine Iodide (PTC) shows that the apparent Michaelis-Menten (Km app) of the partially purified enzyme was 0.1265 mM and the apparent maximal velocity (Vmax app) was 0.6981 μmol/min/mg, with a substrate specificity in the order of acetylthiocholine iodide (ATC) > propionylthiocholine iodide (PTC) > butyrylthiocholine iodide (BTC). This, strongly suggest that AChE was the main bulk of the successfully bound and purified enzyme for this column. Sodium dodecyl sulphate - Polyacrylmide gel electrophoresis (SDS-PAGE) carried out shows a greatly reduced number of band in the gel, again fortified the efficiency of the procainamide-based affinity chromatography column in obtaining a highly partial purified AChE. Temperature optimization studies show that the AChE has an optimum activity at 25°C. Primary and secondary screening of 16 xenobiotics comprising 11 pesticides and 5 solvents shows that 8 pesticides and no solvents show inhibition effect on AChE. Further studies with eight of the xenobiotics shows that, partially purified AChE exhibits more sensitivity to the xenobiotics than crude AChE. Half life (IC50) studies carried out show that different sources of AChE have different sensitivities towards individual insecticides. Meanwhile, comparison between P. pangasius and E. electricus AChE shows that AChE from P. pangasius is more sensitive to carbofuran (0.0025 mg/l), carbaryl (0.0544 mg/l), methomyl (0.0124 mg/l), parathion (0.0401 mg/l), diazinon (0.1112 mg/l) and chlorpyrifos (0.0176 mg/l), while E. electricus is more sensitive to bendiocarb (0.0193 mg/l) and malathion (0.0278 mg/l). Comparison of the insecticides relative sensitivity of AChE from within each source revealed that both fish AChE (P. pangasius and E. electricus) have more similarity in insecticides sensitivity rank order compared to insect (M. domestica). Copper, silver and mercury show 58%, 68% and 86% inhibition of AChE respectively while lead, cadmium and arsenic did not inhibit AChE at 10 mg/l. Half life (IC50) studies carried out show that E. electricus is a better indicator for all three heavy metal compared to partially purified AChE from P. pangasius. The result shows that AChE from P. pangasius have the potential to be used as an environmental bioindicator for the detection of selected insecticides and heavy metals.